Development Mode of Recreation Belt around the City: Ecological Authenticity or Fashion Creativity? - Liang Zhao; Yuanyuan Shen; Nailin Gu; Jingyu Dai (Bioinorganic Chemistry and Applications)
The recreational belt around the city has low population density, good ecological environment, and rich natural and cultural landscapes, which can meet the tourism needs of urban residents to get close to nature and experience culture. Particularly in today’s increasingly normal epidemic prevention and control, outing and microtourism have become the first choice of urban public tourism and an important part of rural tourism development. In the process of developing rural tourism, there are two distinct voices: one is to pay attention to the local complex and strive to let people “see mountains and water and remember nostalgia.” In the era of cultural tourism integration, we should promote rural tourism with culture, highlight rural culture with rural tourism, and give full play to the bridge between cultural tourism and rural cultural innovation. In view of this situation, this paper discusses the theme orientation of the advanced development of the recreational belt around the city through three studies. In Study 1, tourists’ perceptions of local complex and rural cultural creation were compared through field investigation. In Study 2, brand trust was used as a calibration variable to further test the robustness of the conclusion. Study 3 analyzed the “distortion” mechanism of rural cultural creation and tested the intermediary effect of psychological distance. At the same time, it discusses the evolution model of the recreational space system around the city. The development of recreation space shows that the recreation space around the city is the product of the agglomeration of population and economic activities, and its occurrence and development process is closely related to the expansion of urban space and the change of human living space. This paper analyzes the spatial process of the development of recreation around the city, focuses on the types of recreation space that continue to appear in the development and evolution of modern recreation space, and then tries to find the context of the gradual development and evolution of recreation around the city with the process of urbanization and excavate the organic connection between the recreational space and the city and its surrounding areas in the process of development and evolution. It is found that (1) tourists’ perception of local culture is further distorted, which leads to a further reduction in tourists’ perception of “local culture” and “recreation,” and (2) the increase in psychological distance is the key psychological mechanism for tourists to perceive “lost property.”